PERENCANAAN STRUKTUR GEDUNG MENARA BRI SEMARANG - Permatasari, Linda; W., Rahadhiyan Putra; Sabdono, Parang; Wibowo, Hardi (Jurnal Karya Teknik Sipil, 2014)
The structural of BRI tower building Semarang is designed in seismic zone of Semarang city, which is designed by using the Special Moment Resisting Frame System (SMRFS) based on ”Indonesian Concrete Code (SNI 03-2847-2002)”, while the analysis of earthquake load uses response spectrum method based on “Indonesian Seismic Code(SNI 03-1726-2012). The design structural of BRI tower building Semarang using“Capacity Design” concept. As for using this concept has purpose what if strong earthquake happens, that cause forms plastic hinge on structural elements which is desired appeared on the beams. To guarantee plastic hinge happens on the beams, so the columns must be designed stronger than the beams (Strong Column Weak Beam Concept). The analysis of the structure is using SAP2000 computer program  version 14. As the result of calculations showed that structural element of BRI tower building is safe based on analyze.